Opoptera Aurivillius, 1882 (Lepidoptera: Nymphalidae, Satyrinae, Brassolini): Taxonomic revision, molecular phylogeny and description of a new species - Cajé, Suianne; Casagrande, Mirna Martins; Piovesan, Mônica; Lamas, Gerardo; Mielke, Olaf Hermann Hendrik (Zootaxa, 2025)
Opoptera Aurivillius, 1882 (Lepidoptera: Nymphalidae, Brassolini) is a Neotropical genus, with species occurring from Mexico to Argentina. Although previous phylogenetic hypotheses involving Opoptera species have been proposed, an investigation of the species relationships based on molecular data, supported by a systematic review, has not been carried out to date. This study presents a taxonomic revision of Opoptera, which currently comprises eight species and two subspecies, proposing a hypothesis of relationships among the taxa based on DNA, morphology, geographic distribution, and natural history data. To carry out this study, 530 specimens of all species of the genus were examined, including type material of all proposed taxa. For the phylogenic hypothesis, the maximum likelihood method was used, and five molecular markers: one mitochondrial, cytochrome c oxidase subunit I (COI), and four nuclear, elongation factor 1-alpha (EF-1α), ribosomal protein S5 (RpS5), wingless (wg), and glyceraldehyde-3-phosphate dehydrogenase (GAPDH). Opoptera was recovered as monophyletic and the relationships between species corroborate the previous hypotheses. From the taxonomic review, two synonyms are proposed: Opoptera hilaris colombiana (Rothschild, 1916) syn. nov. and Opoptera hilaris fuscata Stichel, 1908 syn. nov. of Opoptera hilaris Stichel, 1901. A new status is proposed: Opoptera mexicana J. Maza & R. G. Maza, 1989 stat. nov. A new species is described: Opoptera iracildae sp. nov. In order to stabilize the nomenclature of the group, three neotypes are designated for Caligo syme Hübner, [1821], Opsiphanes arsippe Hopffer, 1874, and Opoptera aorsa hilaris Stichel, 1901; and ten lectotypes for Morpho aorsa Godart, [1824], Opoptera aorsa litura Fruhstorfer, 1907, Opoptera arsippe bracteolata Stichel, 1901, Opoptera aorsa fuscata Stichel, 1908, Opsiphanes sulcius Staudinger, 1887, Opsiphanes sulcius var. sodalis Röber, 1906, Papilio alcimedon Dalman, 1823, Morpho acadina Godart, [1824], Opoptera syme fumosa Stichel, 1902, and Opsiphanes staudingeri Godman & Salvin, 1894. This study recognizes ten valid species and eight synonyms.